How important are maritime emissions for the air quality: at European and national scale - Monteiro, A. (2018)
Due to its dependence on fossil fuel combustion, emissions from the marine transport sector can significantly contribute to air pollution. This work aims to evaluate the impact of maritime transport emissions on air quality in Portugal using a numerical air quality modelling approach, with high-resolution emission data. Emissions from the European TNO inventory were compiled and pre-processed at hourly and high spatial (∼3 × 3 km2) resolutions. Scenarios with and without these maritime emissions were then simulated with the WRF-CHIMERE modelling system, extensively tested and validated for Portugal domain, in order to evaluate their impact on air quality. A simulation was performed for one year (2016) and the resulting differences were analysed in terms of spatial distribution, time series and deltas. The main deltas for NO2 and PM10 are located over international shipping routes and major ports, while O3 concentrations are impacted in a larger area. The modelling results also indicate that shipping emissions are responsible for deltas in the concentration of NO2 higher than 20% over specific urban areas located in the west coast of Portugal, and less than 5% for PM10. For O3 the relative contribution is low (around 2%) but this contribution is also observed at locations more than 50 km from the coast.